Empowering the Local Economy Through Strategic Development of a Household-Based Carica Beverage Industry in Gembol Village Pejawaran Subdistrict Banjarnegara Regency - Putri, Febriliana; Nuafal, Muhammad; Risawandi R, Muh. Syahlan (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2025)
In the field of economics and social development, home industries play a significant role in enhancing and fostering community creativity and innovation, as well as in reducing social inequality. Within the scope of home industries, various development approaches exist, such as the Tropico carica beverage industry located in Gembol Village. In addition to serving as a side business for its owner, Tropico also provides a source of income for several housewives in the village. This study aims to describe the strategies and challenges involved in developing the carica beverage business and how it contributes to improving household economies in Gembol Village. The research employed a qualitative descriptive method, with data collected through observation, interviews, and documentation. The results show that strategies for developing the carica beverage business to improve household economies include product innovation, sustainable strategies, and networking strategies through resellers. The challenges in developing the business involve both internal and external factors. Internal factors include decreased demand after Eid, limited production capacity, and a consignment system. Meanwhile, external factors consist of product competition, price competition, lack of knowledge in using information technology, and the seasonal availability of raw materials